Prevalence of Glucose Intolerance in Women with Polycystic Ovary Syndrome: Experience from a Tertiary Care Hospital - Laila, Rona; Mahmud, Nusrat; Nargis, Monnujan; Chowdhury, TA (BIRDEM Medical Journal, 2016)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting 5-10% women of reproductive age. The prevalence of abnormal glucose tolerance (impaired fasting glucose, IFG, impaired glucose tolerance, IGT and type 2 diabetes mellitus, T2DM) in women with PCOS is substantially higher than expected when compared with age and weight-matched population of women without PCOS. The present study was conducted among women of reproductive age with PCOS to characterize the extent and nature of glucose intolerance. Methods: This observational study was conducted in Centre for Assisted Reproduction (CARE), Department of Obstetrics and Gynaecology and Biomedical Research group, BIRDEM from January 2006 to December 2008. Results: Total number of patients was 103 and their age ranged between 15 and 36 years. Fifty percent of them were overweight or obese. IGT and T2DM were present in 29.1% and 4.9% cases respectively. Body mass index (BMI) of patients with T2DM with PCOS was significantly higher than normal glucose tolerance (NGT) group (p=0.005). There was no difference of BMI between NGT, with IGT and IGT with T2DM with PCOS. Diabetic PCOS women were older than NGT and IGT group (p=0.002, p=0.009 respectively). Family history of diabetes was present in 80% diabetes PCOS compared to 63.3% in IGT and 39.7% of NGT with PCOS. Conclusions: PCOS women have significantly increased prevalence of IGT and T2DM. Obesity and age substantially increase risk of glucose intolerance but IGT and T2DM can develop independent of obesity in PCOS women. Birdem Med J 2016; 6(1): 36-39